2021
DOI: 10.1111/jog.14891
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Magnetic Resonance Imaging versus Intraoperative Frozen Section Diagnosis for Predicting the Deep Myometrial Invasion in Endometrial Cancer: Our Experience and Literature Review

Abstract: Aim: The present study was designed to directly compare the diagnostic performance of preoperative magnetic resonance imaging (MRI) and intraoperative frozen section (FS) diagnoses in predicting deep myometrial invasion (MI) of endometrial cancer. Methods: Using MRI findings and FS diagnoses, 194 patients with surgically staged endometrial cancer were evaluated for deep MI between 2006 and 2018. Definitive histological diagnosis of paraffin sections of excised tissues was used as the gold standard approach. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Further, specificity of intraoperative diagnosis was higher than that of preoperative biopsy when there was no myometrial invasion. While Iitsuka et al 23 suggested the efficacy of both MRI and intraoperative diagnosis especially focusing on cases with more than 1/2 myometrial invasion, our study suggests that intraoperative diagnosis is also useful in cases with none or less than 1/2 myometrial invasion. The concordance rate was expected to increase as the number of sections increased.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Further, specificity of intraoperative diagnosis was higher than that of preoperative biopsy when there was no myometrial invasion. While Iitsuka et al 23 suggested the efficacy of both MRI and intraoperative diagnosis especially focusing on cases with more than 1/2 myometrial invasion, our study suggests that intraoperative diagnosis is also useful in cases with none or less than 1/2 myometrial invasion. The concordance rate was expected to increase as the number of sections increased.…”
Section: Discussioncontrasting
confidence: 56%
“…Further, specificity of intraoperative diagnosis was higher than that of preoperative biopsy when there was no myometrial invasion. While Iitsuka et al 23 was expected to increase as the number of sections increased.…”
Section: Discussionmentioning
confidence: 94%
“…3,15,20 Iitsuka et al in their study and review of literature found that their data and the pooled analysis with previous studies indicate that the frozen section diagnosis is sensitive as MRI assessment in predicting deep MI, and has a higher specificity compared with MRI. 27 Contraindications for MRI should also be kept in mind, when MRI cannot be performed such as metal foreign body, pathologic obesity, contrast allergies and claustrophobia.…”
Section: Discussionmentioning
confidence: 99%
“…in their study and review of literature found that their data and the pooled analysis with previous studies indicate that the frozen section diagnosis is sensitive as MRI assessment in predicting deep MI, and has a higher specificity compared with MRI. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Preoperative MRI reveals myometrial invasion almost as accurately as examination of frozen sections. 18 In patients with endometrioid-type grade 1 EC, the risk of myometrial invasion evident in the postoperative hysterectomy specimen is less than 1% if such invasion has not been detected by MRI. 19 Therefore, the specificity of MRI is high in such cases.…”
Section: Discussionmentioning
confidence: 99%